DETERMINING THE VENDING MACHINE PURCHASING EXPERIENCE TOWARDS CUSTOMER SATISFACTION AMONG UNIVERSITY STUDENTS - Mimi Nadhirah binti Aszhar; Muhammad Amirul Firdaus bin Asri; Noorazlin binti Ramli; Fatimah binti Abd Ghani (International Journal of Accounting, Finance and Business, 2022)
Vending machine utilization can give customers easy, autonomous services and isavailable 24 hours a day. The primary goal of this study is to determine the relationshipbetween vending machine purchasing experiences and customer satisfaction and the mostinfluential determinants. Mode of payment, vending machine condition, vending machinemaintenance, product assortment, and product freshness were evaluated. Data is collected from364 consumers in the UiTM Terengganu campus via an online survey. This study focuses onthree Terengganu campuses: UiTM Dungun, UiTM Bukit Besi, and UiTM Kuala Terengganu.Frequency analysis, descriptive analysis, and multiple regression analysis were performed.Machine maintenance is an essential aspect determining consumer satisfaction whenpurchasing via vending machines. As a result, the findings of this study can assist vendingmachine retailers in preserving customer loyalty, acquiring new consumers, and helping thecompany to thrive in the future.